Brand Avoidance: Relations Between Brand-related Stimuli and Negative Emotions - Kavaliauskė, Monika; Simonavičiūtė, Edita (Organizations and Markets in Emerging Economies, 2015)
The article analyses one of the parts of anti-consumption phenomenon – brand avoidance. Most of the research on the topic of brand avoidance is usually qualitative, analysing only singular brand avoidance reasons, whereas this article employs a quantitative method to analyse brand avoidance, including different brand-related stimuli (unmet expectations, symbolic incongruence, unacceptable trade-off, ideological incompatibility) and the negative emotions (dislike, anger, worry, embarrassment) consumers feel towards brands. What is more, this research is the first to analyse brand avoidance in the context of emerging markets, as previous studies were carried out in Western countries. However, it was found that different brand-related stimuli have positive relations mainly with dislike emotion, which was the only one influencing brand avoidance.